EKSPLORASI JAMUR MAKROSKOPIS DI HUTAN OELUAN KABUPATEN TIMOR TENGAH UTARA - Lukas Pardosi; Florian Mayesty Prima Makin; I Gede Arya Wiguna (Saintek Lahan Kering, 2020)
Research on the diversity of macroscopic fungi in the Oeluan Forest area of ​​North Central Timor district has never been reported. This research was conducted in January 2020 with a geographical location of 9° 2¢ 48 "LS-9° 37¢ 36" LS124° 4¢ 2 "BT-124°46¢ 0" BT, this research was carried out on four different lines. The length of the observation path is 100 m. The method used in each observation lane in each method is the roaming method and purposive sampling, based on the presence of macroscopic fungi that are considered to represent the area, after that it is continued by recording the number of individuals, collections and documentation. Observation and collection of species is carried out exploratively. From the results of the study found 9 species of macroscopic fungi namely, Ganoderma aplatum, Earliella scabrosa, Polyporus tenuiculus, Polyporus squamosus, Mikroporus xanthopus, Favolus grammocephalus, Pycnoporus cinnabarinus, Ganoderma lucidium, Laccaria vinaceoavellaneae